Persistent inflammation worsens short-term outcomes in massive stroke patients - Hou, Duanlu (BMC Neurol, 2021)
BACKGROUND: Persistent inflammation is an important driver of disease progression and affects prognosis. Some indicators of inflammation predict short-term outcomes. The relationship between prognosis, especially mortality, and persistent inflammation in massive stroke has not been studied, and this has been the subject of our research. METHODS: From April 1, 2017 to February 1, 2020, consecutive patients were prospectively enrolled. Clinical data, laboratory data, imaging data and follow-up infections morbidity were compared between 2 groups according to modified Rankin scale (mRS) scores (mRS < 3 and ≥ 3) at 1 month. The binomial logistic analysis was used to determine independent factors of 1-month prognosis. Short-term functional outcome, mortality and infection rates in massive stroke with and without persistent inflammation were compared. RESULTS: One hundred thirty-nine patients with massive stroke were included from 800 patients. We found that admission blood glucose levels (p = 0.005), proportions of cerebral hemispheric (p = 0.001), posterior circulatory (p = 0.035), and lacunar (p = 0.022) ischemia were higher in poor outcome patients; neutrophil-to-lymphocyte ratio (odd ratio = 1.87, 95%CI 1.14–3.07, p = 0.013) and blood glucose concentrations (odd ratio = 1.34, 95%CI 1.01–1.79, p = 0.043) can independently predict the short-term prognosis in massive stroke patients. We also found that the incidence of pulmonary infection (p = 0.009), one-month mortality (p = 0.003) and adverse outcomes (p = 0.0005) were higher in patients with persistent inflammation. CONCLUSIONS: This study suggested that persistent inflammation is associated with poor prognosis, 1-month mortality and the occurrence of in-hospital pulmonary infection and that higher baseline inflammation level predicts short-term poor outcomes in massive stroke. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12883-021-02097-9.